The Impact of the Digital Economy on the Growth of MSMEs in Indonesia - Kukuh Lukiyanto (Archipel: Journal of Indonesian Interdisciplinary Studies, 2025)
The digital economy has become a catalyst for structural changes in businesses, significantly impacting the growth of MSMEs in Indonesia by improving market access, operational efficiency, and financial inclusion. This study uses a qualitative approach based on a literature review to integrate empirical and conceptual findings related to the adoption of digital platforms, electronic payment services, digital literacy, and relevant government policies. Thematic synthesis reveals that digital technology adoption accelerates the expansion of consumer reach and enables more efficient supply chain management, but disparities in literacy and infrastructure are key barriers that reduce potential benefits for some MSMEs. The role of fintech and digital payment services increases financial inclusion but demands managerial capacity and data protection. Targeted policy interventions—including training, digital financing facilitation, and infrastructure development—appear crucial to narrowing the adoption gap. The findings highlight the need for regular evaluation of digitalization programs to align them with local needs and business characteristics. Research recommendations include longitudinal studies to measure the long-term effects of digitalization on productivity, business resilience, and local economic equity. The results of this study provide a policy basis for improving the effectiveness of MSME digital transformation.